Alcohol-Soluble, Sulfonated Poly(arylene ether)s: Investigation of Hydrocarbon Ionomers for Proton Exchange Membrane Fuel Cell Catalyst Layers. Issue 6 (27th February 2015) - Strong, Aaron; Britton, Benjamin; Edwards, Dave; Peckham, Timothy J.; Lee, Hsu-Feng; Huang, Wen Y.; Holdcroft, Steven
Abstract : Novel sulfonated poly(arylene ether)s, characterized as being highly sterically encumbered, were synthesized for investigation as the ionomer in proton exchange membrane fuel cell (PEMFC) catalyst layers. Catalyst-coated membranes were prepared via their incorporation into alcohol-based catalyst inks, devoid of the high-boiling, polar aprotic solvents typically required for hydrocarbon-based ionomer inks. Catalyst layers thicknesses increased from 8.5 to 9.1 μm when the hydrocarbon ionomer loading was increased from 20 to 40 wt%, but resulted in a 77% loss in pore volume for fully hydrated electrodes. The catalyst layers possessed similar electrochemical surface areas and net ionic conductivity, yet catalyst layers containing 20 wt% ionomer yielded the highest overall fuel cell performance and considerably outperformed catalyst layers prepared from inks that contained high-boiling solvents.